CONSTITUTIONAL REVIEW OF THE RIGHT TO EDUCATION: AN ANALYSIS OF CONSTITUTIONAL COURT DECISION NO. 3/PUU-XXII/2024: TINJAUAN KONSTITUSIONAL TENTANG HAK ATAS PENDIDIKAN: ANALISIS KEPUTUSAN MAHKAMAH KONSTITUSIONAL NOMOR 3/PUU-XXII/2024 - Rengga Kusuma Putra; Retno Saraswati; Bagus Hermanto; Lita Tyesta Addy Listya Wardhani; Satriya Nugraha (Pusat Studi Konstitusi dan Perundang-undangan, 2026)
Decision No. 3/PUU-XXII/2024 of the Constitutional Court of the Republic of Indonesia represents a significant development in the trajectory of Indonesian legal politics, particularly in relation to right to education as the constitutional protection enshrined in the 1945 Constitution. Although the ruling carries substantial implications for the interpretation of state obligations in the education sector, scholarly discussion has largely focused on the doctrinal aspects of constitutional adjudication, leaving limited attention to the broader fiscal and political implications of the decision within Indonesia’s governance framework. This study therefore seeks to examine the constitutional meaning and policy consequences of the ruling through a descriptive qualitative approach, with particular attention to the normative structure of the Court’s reasoning and the social justice values underlying its interpretation. The analysis focuses on how the Constitutional Court articulates the relationship between constitutional mandates, state responsibility, and the protection of individual educational rights within the broader framework of Indonesia’s welfare-oriented constitutionalism. The findings indicate that Decision No. 3/PUU-XXII/2024 strengthens the constitutional status of education as a positive right that requires active state intervention. At the same time, the ruling clarifies the scope of governmental obligations in ensuring equitable access to education while implicitly raising questions regarding fiscal allocation, institutional capacity, and policy prioritisation in the implementation of constitutional guarantees. By situating the decision within the broader discourse on the political theory of education law and the adjudication of socio-economic rights, this article contributes to the development of a normative framework that understands education not purely as a matter of public policy but as a constitutionally mandated instrument for achieving social justice. Ultimately, the study argues that the decision reflects a more responsive orientation in Indonesian legal politics, one that seeks to align constitutional interpretation with the pursuit of substantive equality in the national education system.